AN ANALYSIS OF THE INDIRECT BOUNDARY ELEMENT METHOD FOR SEISMIC MODELLING - Karabulut H.; Ferguson J.F. (My University, 2001)
An indirect boundary element method has been used to compute seismic wavefields in layered media. The advantages of this technique over numerical grid methods are that it satisfies radiation conditions, incorporates free surface effects, solves viscoelastic problems and can handle arbitrary source types. The technique is more appropriate for models with high aspect ratios and a limited number of layers. The computational cost increases with the number of layers and frequency content. Examples are presented in this study to illustrate some of the features of the technique. Seismograms are computed for SH and P-SV line sources in 2-D earth models. Finite-difference and the Cagniard-de Hoop methods are used to test the accuracy of the technique. Even though the computation time for the method is several times greater than finite differences, the technique becomes cost effective as the number of computed shot-gathers increases. The technique also allows computation of constant offset gathers at a small additional cost which is very expensive to do by using finite differences.
Keywords: BOUNDARY ELEMENT; FINITE DIFFERENCE; HUYGENS PRINCIPLE; SEISMIC WAVES